Evaluasi Kesesuaian Lahan untuk Pengembangan Tanaman Kayu Putih (Malaleuca leucadendra) pada Kawasan Hutan Produksi Bali Barat (Kecamatan Grokgak) Kabupaten Buleleng Bali - DIBIA, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 5 No 2 (2015), 2015)
Evaluation of Land Suitability for Development of Cajuput Tree at Area of ProductionForest in West Bali, District of Grokgak, Buleleng Regency, Bali. The objective of theresearch was to investigate and to map the land suitable level with limiting factor, also to givedirection or recomendation on kajuputi development in research area. The research used landevaluation survey method. Sample taking cunducted by stratified purposive sampling withland unit stratum. Land quality that observed include temprature/average temprature yearly,water availability, rooting media, nutrient retention, nutrien availability, salinity,terrain/mechanitation potential, and erosion danger level. Land suitable classificationconducted by matching between land quality with crop requirement of kajuputi (map inatachment). The result showed that actual as well as potential land suitable and kajuputidevelopment range from moderate suitable (S2), marginal suitable (S3), and not suitable (N)with limiting factor: duration of drymonth, pH, efective soil depth, slope, and erosion dangerlevel, stoniners and rockoutcrop. The effort that could be sugested for land management wereimproving organic matter to decrease high pH and aplication of terasering to spriest erotion.
Keywords: Land suitable, land quality, land characteristic, cajuput